Study of new onset cutaneous manifestations in Rheumatic Diseases - Archana Sonawale; Nilakshi Sabnis; Nirmal Bankar (International Journal of Medical Research and Review, 2018)
Background: Skin manifestations are an important clue to underlying rheumatological conditions and at times the first manifestation of the disease. Their identification helps in diagnosis, classification and follow up of these diseases. Hence we conducted this study to assess the new onset cutaneous lesions in patients with rheumatic diseases and correlate skin lesions with disease activity and study the response to therapy over a period of 3 months.Materials and Methods: This prospective observational study was done in KEM Hospital, Mumbai over 18 months recruiting 78 patients, presenting to Rheumatology OPD / wards with new onset skin manifestations. Disease activity was calculated as per standard indices for each rheumatological disease. Skin lesions appearing due to adverse effects of drugs or unrelated to the disease were excluded from the study. The outcome of the skin lesions was assessed at 3 months follow up.Results: Mean age of patients was 38 years with 91% being females. SLE was the most common diagnosis. The most common skin lesions were malar rash among SLE patients; rheumatoid nodules in patients of RA; Sclerodactyly in the Scleroderma patients and Heliotrope rash amongst the dermatomyositis patients. The mean SLEDAI score in the group with LE non -specific lesions was significantly higher compared to the group with LE-specific lesions (P<0.0001). At 3 months there was statistically significant reduction in SLEDAI score after treatment in SLE patients. In patients of RA, 74% patients showed reduction in DAS 28 ESR score with treatment at 3 months. Systemic sclerosis patients failed to show significant improvement in Modified Rodnan’s Skin Score after 3 months of treatment.Conclusions: Among all rheumatological conditions SLE presents most often with skin involvement. Patients with LE specific lesions have lower disease activity (SLEDAI score) as compared to LE nonspecific lesions. At 3 months follow up the response to treatment is good in SLE patients with reduction in SLEDAI scores and also in RA patients with reduction in DAS 28 ESR scores.